Predicted impact of climate change on coffee-supply chains - Läderach, Peter R.D.; Lundy, Mark M.; Jarvis, Andy; Ramírez Villegas, Julián Armando; Pérez, P.E.; Schepp, Kathleen; Eitzinger, Anton (Springer, 2010)
Global circulation models all forecast that climate change will increase mean temperatures and change precipitation regimes. As a result, traditional coffee growing regions may disappear and new regions may appear. At the same time, demand for high quality, responsibly sourced coffee continues to grow globally. For sustainable sources of coffee, participants in the global coffee supply chain need to know where coffee will grow in the future and how the suitability of these areas will change over time. With this information, the supply chain then needs to develop appropriate site-speciﬁc mitigation and adaptation strategies for both the short and the long term, to guarantee coffee supply as well as to support improved livelihoods for rural communities. In this paper, we ﬁrstly quantify the impact of climate change on the suitability of land to grow coffee in a case study in Nicaragua and on acidity content of beverage coffee in a case study in the Veracruz Department of Mexico. Secondly, we propose site-speciﬁc adaptation strategies and ﬁnally identify critical potential impacts of climate change on the overall supply chain and the implications for all actors in the system. We conclude the paper by identifying key directions for future research to seek mitigation and adaptation strategies at both the community and the supply-chain level.